Fermentasi alkohol dari nira aren (Arenga pinnata Merr.) dengan menggunakan metode fed batch - D. Ch. Amema; T. Tuju; H. Rawung (Universitas Sam Ratulangi, 2017)
ABSTRACTThis study aims to measure or calculate total microbial, alcohol content, sugar content, pH, temperature, during the process of fermentation of nira aren by using fed batch method. Fermentation of nira aren is done for 10 hours to get alcohol content from nira aren fermentation by using fed batch method, alcohol content obtained 8.33%. In this study parameters that have been observed are sugar content, alcohol content, the amount of microbial biomass, pH, temperature.The results showed that the sugar content for 10 hours decreased from 12.17% -6.00%, the alcohol content during fermentation of nira aren within 10 hours increased from 0.33% -8.33%, then total microbial during fermentation increased from the first hour of 16.00 to the eighth hour of 1780.00, then the ninth hour down 1693.33 to the tenth hour 1493.33. For pH during fermentation of nira aren in time decrease from pH 7-4,00, and temperature during fermentation of nira aren is around 25 0C-27 0C.Keywords: Nira aren, Fermentation, Alcohol, Fed batch